Hubungan Keadilan Distributif Dan Perilaku Kerja Kontraproduktif Pada Karyawan Indomaret Di Kota Bengkulu - Anggri Puspita Sari; Slamet Widodo (Management Insight: Jurnal Ilmiah Manajemen, 2018)
The fact that there is still work in the field that can hamper the performance of human resources, such as contraproductive behavior. Behavioral contraproductive behavior is a serious problem that can also harm the organization as a whole. At Indomaret in Kota Bengkulu it self, some time ago there had been cases of price differences listed on the shelf of goods and on the scanner machine connected at the checkout counter. In addition, the cashier there is a mistake to record the goods purchased by consumers into two pieces causing a double payment. The purpose of this study is to determine the relationship of distributive justice and contraproductive work behavior on Indomaret employees in the city of Bengkulu. The sample of research is Indomaret employee in Bengkulu city. Data collection technique in this research is hand delivery by using questionnaire. The data has been collected and then analyzed using qualitative analysis approach. The result of research shows that there is a negative correlation between distributive justice and contraproductive work behavior to Indomaret employees. The relationship between distributive justice and contraproductive work behavior which is a negative relationship means that if distributive justice is perceived by the employee, then the likelihood of employees engaging with contraproductive behavior will be small.Keywords: Distributive justice, contraproductive work Behavior, Store leader, Indomaret Employee.